My doll, my style : sewing fun fashions for your 18-inch doll - Allen, Anna (The Quilting Company, an imprint of F+W Media, Inc., 2018)
"Sew stylish doll clothes with confidence. When off-the-rack doll clothes just won't do, discover how fun and easy it is to make custom, on-trend fashions your child will love. In My Doll, My Style, designer and Doll it Up blogger Anna Allen shows you how to create runway-worthy looks for 18-inch dolls. From jeggings and dresses to shorts and tees, each pattern is designed for today's fashion fabrics with a modern aesthetic and fit."--Page [4] of cover.